SPHERE OF LEGAL REGULATION: PROBLEMS OF DEFINITION AND CORRELATION WITH SUBJECT OF LEGAL REGULATION - Вашкевич, Светлана (Teisė, 2017)
The article studies the problem of defining the sphere of legal regulation, which is urgent for modern jurisprudence. It considers different authors‘ approaches to the definition of this category. A correlation of the sphere of legal regulation with such an allied legal category as the subject of legal regulation is carried out. The author’s position on prohibiting of identification of the sphere and the subject of legal regulation is stated.